True to type?: EU-style date marking and the valuation of perishable food - D'Amato, Alessio; Goeschl, Timo; Lorè, Luisa; Zoli, Mariangela (Food policy, 2023)
Date marking is intended to help consumers make informed food safety and quality choices when confronted with perishable food products. We provide causal in-store evidence on how EU-style date marking (best before and use by) influences consumers’ valuation of perishable food around the expiry date. In a preparatory survey (n=100), we first identify perishable food items amenable to experimental manipulation. A modified multiple price list (MPL) experiment (n=200) then tests shoppers’ valuation of perishable food with expiry dates in the future and the past. We vary date mark type (use-by versus best-before) and information status (with and without education) while preventing free disposal censoring. We find that expiry dates affect consumer valuation. Variation in date mark type has little practical relevance. Educating consumers about the meaning of date mark types reduces willingness to pay for potentially unsafe food, but does not increase it for more durable items. An attentiveness experiment (n=160) finds that inattention and consumers’ native understanding of current date marks can explain the evidence from the modified MPL experiment. Jointly, these results help explaining existing observational evidence and assessing the prospects of consumer education campaigns.